Since there is no common factor between the numerator and denominator, hence, there is no hole
To get the vertical asymptotes
Equate the denominator to zero
![\begin{gathered} x^2+2x-3=0 \\ (x+1)^2=3+1 \\ (x+1)^2=4 \\ (x+1)=\pm\sqrt[]{4} \\ x+1=\pm2 \\ x=-1-2,-1+2 \\ x=-3,1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/xdmjggmj4fkwzgtz70n3nfrc9lzw0s01wn.png)
The vertical asymptote are x= -3 and x=1
To get the Horizontal asymptote
we will compare the degree of the denominator with that of the numerator
In this case, the degree of the numerator is 2 and that of the denominator is 2.Thus
the degree of the denominator is equal to that of the numerator.
Therefore the vertical asymptote is given by
![\begin{gathered} y=(a)/(b) \\ \text{where } \\ a=\text{ the leading coefficient of the numerator} \\ b=\text{ the leading coefficient of the denominator} \\ In\text{ this case } \\ a=1 \\ b=1 \\ \text{Therefore the vertical asymptote is } \\ (1)/(1)=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qc9toj4lizm1vrat331vx3a5ysswa7no6s.png)
Therefore the vertical asymptote is 1